2011
DOI: 10.1073/pnas.0913021108
|View full text |Cite
|
Sign up to set email alerts
|

Decreased stability and increased formation of soluble aggregates by immature superoxide dismutase do not account for disease severity in ALS

Abstract: Protein aggregation is a hallmark of many diseases, including amyotrophic lateral sclerosis (ALS), where aggregation of Cu/Zn superoxide dismutase (SOD1) is implicated in causing neurodegeneration. Recent studies have suggested that destabilization and aggregation of the most immature form of SOD1, the disulfide-reduced, unmetallated (apo) protein is particularly important in causing ALS. We report herein in depth analyses of the effects of chemically and structurally diverse ALS-associated mutations on the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
145
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(160 citation statements)
references
References 54 publications
11
145
1
Order By: Relevance
“…Both wild-type and ALS-mutant human SOD1 can be induced to aggregate in vitro using a variety of different treatments, including low concentrations of reducing agents such as DTT or glutathione (16 -19), low pH (18,20), structural perturbants such as trifluoroethanol and elevated temperature (21,22), oxidative modification induced by hydrogen peroxide (23), and by long term air exposure leading to cross-linking of nondisulfide cysteines (24). Some of these conditions, notably low pH, elevated temperatures, trifluoroethanol, and incubation in reducing agents, generate aggregates that bear a remarkable resemblance to amyloid fibrils.…”
mentioning
confidence: 99%
“…Both wild-type and ALS-mutant human SOD1 can be induced to aggregate in vitro using a variety of different treatments, including low concentrations of reducing agents such as DTT or glutathione (16 -19), low pH (18,20), structural perturbants such as trifluoroethanol and elevated temperature (21,22), oxidative modification induced by hydrogen peroxide (23), and by long term air exposure leading to cross-linking of nondisulfide cysteines (24). Some of these conditions, notably low pH, elevated temperatures, trifluoroethanol, and incubation in reducing agents, generate aggregates that bear a remarkable resemblance to amyloid fibrils.…”
mentioning
confidence: 99%
“…19 However, variable clinical features and courses, due to the loss of disulfide bonds of SOD1, 20 suggest that other factors may be involved in the pathogenesis of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have used different solution conditions (increased temperature, decreased pH, increased ionic strength, sonication or agitation) to promote the formation of well-structured, fibrillar amyloid aggregates (see 1.2.3) by various forms of SOD1 (Stathopulos et al 2004;Chattopadhyay et al 2008;Chattopadhyay and Valentine 2009;Oztug Durer et al 2009). Other studies have demonstrated soluble oligomer and small aggregate formation by various forms of SOD1 in quiescent, physiologically relevant solution conditions (Vassall, 2011, Hwang, 2010, Banci, 2008. Thus, it is evident that multiple factors can greatly influence protein folding and aggregation and these factors must be considered when investigating the molecular mechanisms of protein aggregation.…”
Section: Factors That Modulate Aggregation Of Polypeptidesmentioning
confidence: 99%